Response of Resistance Exercise-Induced Muscle Protein Synthesis and Skeletal Muscle Hypertrophy Are Not Enhanced After Disuse Muscle Atrophy in Rat - Ato, Satoru; Kido, Kohei; Sase, Kohei; Fujita, Satoshi (Frontiers in Physiology, 2020)
Skeletal muscle disuse rapidly decreases muscle mass. Resistance training (RT) is believed as the most effective way to gain muscle mass via an increase in mTORC1 activity and muscle protein synthesis (MPS). However, it remains unclear whether muscle atrophy by disuse alters the mTORC1 activation and MPS response to an acute resistance exercise (RE) and chronic RT - mediated skeletal muscle hypertrophy. This study investigated the influence of disuse muscle atrophy on the response of mTORC1 activation and MPS to an acute RE. We also evaluated whether disuse muscle atrophy affects the response of RT-induced muscle mass gain. Thirty male Sprague-Dawley rats were randomly divided into control (CON) or hindlimb suspension (HS) groups. A 14-day hindlimb suspension via the tail was used as the model for gastrocnemius muscle disuse in the HS group. Unilateral lower limb muscle contraction using by percutaneous electrical stimulation was used to mimic the stimuli of RE. Ten bouts of RE were performed in 3-week as chronic RT. Our results showed that MPS and mTORC1 activity was unchanged after HS at basal state. However, the ribosomal RNA (rRNA) level was reduced in HS rats compared to that in CON rats at basal state. MPS and rRNA increased in both HS and CON rats in response to acute RE to the same extent. However, the level of mTORC1 activation in response to an acute RE was significantly higher in HS than that in the CON group at 12h after exercise, even though no difference was observed at 3h after exercise. The 10-bout RT significantly increased gastrocnemius muscle mass in both CON and HS rats. The response of muscle hypertrophy did not differ between the groups. Therefore, MPS in response to acute RE and muscle hypertrophy in response to chronic RT were unaltered after disuse muscle atrophy.